A comparison of the combined solar collector efficiency at different modes of its operation - Пона, Остап Миронович; Гулай, Богдан Іванович (Eastern-European Journal of Enterprise Technologies, 2015)
The systems of solar heat supply that use conventional solar collectors are rather expensive. Therefore, at present it is important to improve and create new combined solar collectors in which the absorber of solar energy is made of a corrugated roofing material. This allows reducing the cost of a solar collector, increasing its strength and simplifying its structure. The paper suggests increasing the productivity of solar energy use by means of combining a solar collector with a building roof. We present our research findings on incoming solar radiation onto the combined solar collector. We have determined the graphic dependence between various orientations of the roof-based solar collector and its efficiency. The research has proved that efficiency of the combined solar collector without transparent roofing at the change of the angles of heat flow incidence decreases by 40 %, whereas the efficiency of a conventional solar collector decreases by 60 %. We have described the research findings on the impact of air flow upon the operation of the combined solar collector without transparent roofing. We have determined graphic dependencies between various velocities, directions of air flow and efficiency of the solar collector. It has been proved that efficiency of the combined solar collector when exposed to wind decreases by 45 %. We have determined that efficiency of the combined solar collector being exposed to wind is most of all affected by the air velocity, whereas the air flow direction and intensity of the heat flow affect less.